Work-Related Injuries: An Old Problem Revisited in the First Representative U.S. Sample of Home Health Aides. (September 2013) - Houston, Allison; Young, Yuchi; Fitzgerald, Edward F.
Objective: To examine whether certain personal and workplace factors increase risk for work-related injuries among home health aides.Method: A cross-sectional analysis was conducted using data from the 2007 National Survey of Home Health Aides among workers who provided formal caregiving to older adults or people with disabilities ( N = 3, 377, weighted sample = 160, 720).Results: Multivariate logistic regression identified six factors associated with injury: White race (OR = 2.07, 95% CI 1.18, 3.63); inappropriate workload (OR = 3.27, 95% CI 1.55, 6.93); having multiple jobs (OR = 2.73, 95% CI 1.30, 5.71); job dissatisfaction (OR = 2.71, 95% CI 1.23, 5.96); higher hourly pay rate (OR = 2.38, 95% CI 1.31, 4.33); and working in two locations (inpatient facility and patient's home) compared with working in patient's home only (OR = 2.57, 95% CI 1.51, 4.40).Discussion: Interventions should be developed to address preventable risk factors. Evaluations of candidate interventions should control for other related factors that are not modifiable.